Pengaruh Permainan Ular Tangga Huruf Hijaiyah Terhadap Kemampuan Mengenal Huruf Hijaiyah Anak Usia 4-5 Tahun - Latifah, Zabid (Prosiding University Research Colloquium, 2021)
This study aims to determine the effect of the snake ladder game of hijayah letters on the ability to recognize hijayah letters of children aged 4-5 years in RA Perwanida Grabag Grabag District Magelang Regency.This research is a quasi-experimental research. The variables used in this study were the game of snakes and ladders hijaiyah letters as the independent variable and the ability to recognize hijaiyah letters for children aged 4-5 years as the dependent variable. The population in this study were all students of group A in RA Perwanida Grabag totaling 90 children. The sampling technique used saturated sampling technique, so that a sample of all students in group A RA Perwanida Grabag, totaling 90 children, was divided into two groups, 46 as the experimental group and 44 as the control group. Methods of data collection using observation techniques. The data analysis technique used statistical non parametric Mann Whitney test.The results of the study concluded that the game of snakes and ladders hijaiyah letters had a positive effect on the ability to recognize hijaiyah letters for children aged 4-5 years. This is evidenced by the acquisition of the Mann Whitney test value with a calculated z value of -5.947 with a probability value of 0.000 < 0.05. The results of the study can be concluded that the game of snakes and ladders hijaiyah letters affects the ability to recognize hijaiyah letters for children aged 4-5 years.